Repeated batch fermentation for photo-hydrogen and lipid production from wastewater of a sugar manufacturing plant - Thitirut Assawamongkholsiri (2019)
© 2017 Hydrogen Energy Publications LLC Hydrogen and lipid production from sugar manufacturing plant wastewater (SMW) by Rhodobacter sp. KKU-PS1 were investigated. Aji-L (i.e., a waste from the process of crystallizing monosodium glutamate) was used as nitrogen source. Batch fermentation was conducted in 300 mL serum bottles with the working volume of 180 mL to investigate the optimal inoculum size by varying the initial inoculum concentration from 0.23 to 0.92 gCDW/L. The photo-fermentation was conducted at an initial pH 7.0 and 25.6 °C with continuously light illumination at 7500 lux. The optimal inoculum size of 0.77 gCDW/L gave the hydrogen production rate (Rm) and lipid production of 5.24 mL H2/L.h and 407 mg lipid/L, respectively. The hydrogen production from SMW was further examined in 1.7-L photo-bioreactor with the working volume of 1.2-L using the optimal condition from batch experiment. A photo-bioreactor yielded 1.73 times higher Rm than that obtained from the fermentation in serum bottles with a greater lipid production of 424 mg lipid/L. Hydrogen production from SMW in the repeated-batch fermentation was further studied by varying the medium replacement ratios of 25, 50–75%. A maximum biomass and lipid concentration of 2.83 gCDW/L and 685 mg lipid/L, respectively were achieved at a medium replacement ratio of 75%. C18:1 (51.2%), C18:0 (24.9%) and C16:0 (9.1%) were found as the major free fatty acid. Lactic acid followed by propionic, acetic and butyric acids containing in SMW were the suitable carbon source for biomass production of KKU-PS1.